Алиса в Стране Чудес - Кэрролл Льюис (Книги - мои друзья, 2017)
Экземпляры: Армязьская библиотека (20180730) / Инвентарный номер: 4787 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: К 98 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)